Comparing the Learning Climate of Al-Makmun's Era and the Indonesian Education System Today - Maulida Turrohmah (Journal of Islamic Education Research, 2024)
This article is written with the aim of knowing and understanding the comparison of the learning climate during the reign of Al-Makmun and the Indonesian education system today. Al-Makmun with his various policies on education could build a conducive learning climate so as to develop science and make that period into the Golden Age of Islam.  On the other hand, education in Indonesia today is also in the spotlight. Indonesia's national education system, which has a structured system and regulations from government policies, also has educational goals to educate the nation's generation. With the curriculum applied and the application of educational technology as well as various and educational problems faced such as uneven education, less competent human resources are a challenge for the government. Based on the existing data, it is possible to compare the learning climate in the AL-Makmun era with the education system in Indonesia today through 4 categories, including in terms of educational objectives, teaching methods and curriculum, educational institutions and the use of educational technology. The comparison aims to understand the advantages of each education system both in the era of Al-Makmun and education in Indonesia today.